2000
DOI: 10.1128/aac.44.1.30-38.2000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of Topical Formulations of Foscarnet and Acyclovir and of 5-Percent Acyclovir Ointment (Zovirax) in a Murine Model of Cutaneous Herpes Simplex Virus Type 1 Infection

Abstract: The topical efficacies of foscarnet and acyclovir incorporated into a polyoxypropylene-polyoxyethylene polymer were evaluated and compared to that of 5% acyclovir ointment (Zovirax) by use of a murine model of cutaneous herpes simplex virus type 1 infection. All three treatments given three times daily for 4 days and initiated 24 h after infection prevented the development of the zosteriform rash in mice. The acyclovir formulation and the acyclovir ointment reduced the virus titers below detectable levels in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…This can be explained as when the virus is inoculated in the skin, where the primary infection occurs; it starts spreading from this site, probably by retrograde axonal flow, to sensory ganglia and the central nervous system. Thereafter, the virus reaches axons that innervate skin within the same dermatome as the inoculation site, spreads via orthograde flow into the skin, and produces herpetic lesions within the affected dermatome (10). On the sixth day, herpetic skin lesions appeared in the form of small vesicles distant from inoculation site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be explained as when the virus is inoculated in the skin, where the primary infection occurs; it starts spreading from this site, probably by retrograde axonal flow, to sensory ganglia and the central nervous system. Thereafter, the virus reaches axons that innervate skin within the same dermatome as the inoculation site, spreads via orthograde flow into the skin, and produces herpetic lesions within the affected dermatome (10). On the sixth day, herpetic skin lesions appeared in the form of small vesicles distant from inoculation site.…”
Section: Resultsmentioning
confidence: 99%
“…Murine model of cutaneous HSV-I infection was used to study the antiviral effect of ACV microemulsion. HSV-I propagated in Vero cells (African green monkey kidney cells) in minimum essential medium and female BALB/c mice (5-7 weeks old) were used in this study (10). The plaque assay was performed to check the viral infectivity (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the inoculation of HSV-1 strain F in the lumbosacral area of hairless mice (zosteriform model) was associated with an approximately 50 to 60% mortality rate among untreated infected mice (26,27). The efficacies of gel formulations containing foscarnet, alone or in combination with SLS, given 6 or 24 h after virus inoculation reduced to a similar extent the development of herpetic orofacial lesions.…”
Section: Vol 45 2001 Topical Formulations Against Hsv-1 Infectionmentioning
confidence: 90%
“…Previous studies from our laboratory have demonstrated that the efficacy of 5% acyclovir incorporated into a polymer composed of polyoxyethylene and polyoxypropylene was better than that of the commercial acyclovir ointment (Zovirax) in reducing the development of herpetic skin lesions in mice after a single application 24 h postinfection (27). The improved efficacy of the gel formulation of acyclovir was attributed to the semiviscous character of the polymer, which allows a more efficient drug penetration into the skin.…”
mentioning
confidence: 97%